2022
DOI: 10.24071/llt.v25i2.5221
|View full text |Cite
|
Sign up to set email alerts
|

Reading Anxiety of Efl Learners in Indonesian Rural Schools: A Quantitative Study

Abstract: The purposes of this current study were twofold. First, it attempted to find out the level of reading anxiety among EFL learners in rural schools. Second, it sought to determine whether there is a statistical difference in reading anxiety between rural EFL learners across gender and level of study. Seventy-seven EFL learners from several rural Indonesian schools were involved in completing a 27-items EFL Reading Anxiety Inventory (EFLRAI). The findings revealed different levels of top-down, bottom-up, and clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…As a result, they fail to master the reading context. Thus, it is confirmed that vocabulary and self-confidence are two biggest factors in creating reading anxiety among students (Mudra & Mckinnon, 2022). Guimba and Alico (2015) stated that limited grammatical knowledge and unfamiliar culture contributes to reading anxiety.…”
Section: Findings and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As a result, they fail to master the reading context. Thus, it is confirmed that vocabulary and self-confidence are two biggest factors in creating reading anxiety among students (Mudra & Mckinnon, 2022). Guimba and Alico (2015) stated that limited grammatical knowledge and unfamiliar culture contributes to reading anxiety.…”
Section: Findings and Discussionmentioning
confidence: 86%
“…These factors are a part of domain "lack of vocabulary" and "worrying about the reading effects". In addition, Mudra and Mckinnon (2022) also found that students experience reading anxiety when they do not comprehend grammatical components. As a result, they fail to master the reading context.…”
Section: Findings and Discussionmentioning
confidence: 97%
“…By performing humor in L2 classrooms, it is expected that L2 learners can be happy and laugh, which reduces anxiety in learning English (Fritz, Russek, & Dillon, 2017). Anxiety, according to Mudra and Mckinnon (2022), occurs when EFL students are not aware of their basic competence and they do not attempt to recognize their deeper thoughts. Moreover, humor is also conceptualized as a skill in social life that helps to avoid suffering from tension, relieves satisfaction and pressure apprehension, and raises personality (Pollak & Freda, 1997).…”
Section: Humormentioning
confidence: 99%
“…In line with Harmer (1994) and Pinner (2015) Several previous studies (Allehyani, Burnapp, & Wilson, 2017;Azri & Al-Rashdi, 2014;Huda, 2017) indicates that lecturers have a positive attitude towards authentic materials because the use of authentic materials have several advantages for the students such as increasing students' motivation and giving the opportunity to the students to expose to the real use of language. In Indonesia context, the researcher found several studies regarding the use of authentic materials with different focus such as lecturer's belief in using authentic materials (Kristiana, 2018;Huda, 2017;Mestari & Malabar, 2017), students' perceptions when using authentic materials (Mudra, 2014), and the effect of using authentic materials (Apsari, 2014).…”
Section: Introductionmentioning
confidence: 99%